Development of a rectal sexually transmitted infection – HIV coinfection model utilizing Chlamydia trachomatis and SHIVSF162p3. Issue 3 (25th January 2014) - Henning, Tara; Butler, Katherine; Mitchell, James; Ellis, Shanon; Deyounks, Frank; Farshy, Carol; Phillips, Christi; Papp, John; Patton, Dorothy; Caldwell, Harlan; Sturdevant, Gail; McNicholl, Janet; et al.
Abstract Background Rectal sexually transmitted infections (STIs) may increase HIV susceptibility in men who have sex with men (MSM), and Chlamydia trachomatis is prevalent among HIV‐positive MSM. To study STIs and HIV infection in MSM, we first evaluated whether cynomolgus macaques can sustain both C. trachomatis and SHIVSF162p3 infections. Methods Four SHIVSF162p3‐positive male cynomolgus macaques were used (n = 3 rectally inoculated with 106 IFU; n = 1 control). Systemic and rectal SHIV RNA levels and cytokines were measured by real‐time PCR and Luminex assays, respectively. Results Macaques were successfully Chlamydia infected. Rectal SHIV shedding (P = 0.02 χ2) and levels of G‐CSF, IL‐1ra, IL‐6, IL‐8, IFN‐γ, and TNF‐α (P ≤ 0.01, Mann–Whitney) in rectal secretions increased following infection. Conclusions These pilot data successfully demonstrate rectal C. trachomatis–SHIV coinfection in cynomolgus macaques and suggest the feasibility of a rectal C. trachomatis model for SHIV susceptibility and biomedical prevention studies in the context of rectal STIs.